Multicenter review of impression-based scleral devices. Issue 5 (October 2021) - Nau, Amy; Shorter, Ellen S.; Harthan, Jennifer S.; Fogt, Jennifer S.; Nau, Cherie B.; Schornack, Muriel
Abstract: Objective: To describe outcomes using impression based-scleral devices for the management of anterior segment disease. Methods: Retrospective chart review identified all patients who were fitted with impression-based scleral devices between January 1, 2013 and June 30, 2019 at three specialty contact lens practices. Patient demographic data, indication for device use, visual and physiological outcomes, as well as details of the fitting process and survival of device use were determined. Results: Forty-four patients (70 eyes) were included in the study. Primary indications for device use included corneal irregularity (28 patients, 44 eyes) and ocular surface disease (16 patients, 26 eyes). Fifty-four percent of patients had more than one ocular surface condition, and 39 % of patients had undergone at least one anterior segment surgical procedure. Twenty-nine patients had unsuccessfully attempted to wear standard scleral lenses prior to being fit with impression-based devices. Visual acuity improved significantly with impression-based devices compared to habitual correction (p < 0.001). Completion of the fitting process (including visit to acquire the impression and post-fitting assessments) required an average of 4 [1.5] visits.Ideal haptic alignment was achieved with 74 % and complete limbal clearance was achieved in 83 % of fits. Device use was discontinued due to complications in two eyes. Conclusion: Patients with complex eye disease who are unable to successfully wear standard scleral lenses successfully may achieve visual and therapeutic success with impression-based devices.